Biological evaluation of synthetic aminoglycans as potential antimicrobial and protein delivery agents - Zhang, Xiaolin (Nanyang Technological University, 2023)
Aminoglycans are naturally occurring polysaccharides widespread in both bacteria and mammalian cells, most of which are involved in many essential biological processes. In this thesis, we focused on two types of aminoglycans, GlcNAc-β-1,6-anhydro-MurNAc-peptides (GlcNAc-anhMurNAc-P) and chitosan to explore their potential on biomedical applications. Transglycosylase (TGase) in peptidoglycan (PG) biosynthesis has been considered an attractive antibiotic target. However, current commercial TGase inhibitors all contain lipid tails resulting in poor pharmacokinetics in clinical uses. GlcNAc-anhMurNAc-P are natural PG fragments without lipid chains, chosen as potential substrates of TGase in this study. In vitro TGase assay demonstrated that GlcNAc-β-1,6-anhydro-MurNAc-pentapeptide (GlcNAc-anhMurNAc-AA) and its analogue without peptide were recognized and utilized by bacterial TGase as non-canonical acceptors. The incorporation of GlcNAc-anhMurNAc-AA and its analogue into longer PG strands by TGase terminates the PG glycan elongation, indicating such anhydromuropeptides hold the potential as novel PG-terminating antibiotics. A chitosan-based tumor-targeting nanoparticle was designed for anticancer protein delivery due to limited membrane permeability and tumor selectivity of protein therapeutics. In the nanoparticles, a disulfide linker was equipped to load recombinant Singapore mistletoe lectin A (rSML-A), a ribosome-inactivating protein, and endosome escape peptide, modified Aurein 1.2. In vitro experiments showed efficient intracellular delivery of rSML-A into cancer cells by chitosan-based nanoparticles with dose-dependent cytotoxicity, meanwhile, normal cells were rarely internalized by protein, indicating the effective tumor-selectivity of our nanoparticles. In addition, the LysoTracker staining assay showed successful escape of rSML-A from endosome in the cytosol by nanocarriers. These in vitro studies implied the chitosan backbone-based nanoparticles as efficient tumor-targeting nanocarriers for protein delivery.